B-Spline Solution Of The Black-Scholes Partial Differential Equation - Çağlar, Nazan; İşeri, Müge; Çağlar, Hikmet; Özer, Mehmet (Eudoxus Press, Llc, 1424 Beaver Trail Drive, Cordova, Tn 38016 Usa, 2010)
The numerical solutions of several mathematical models In the financial economics arc arising. Most of the models are based on the Black-Scholes partial differential equations. In this paper, the Black-Scholes option pricing model which has been used frequently is solved by using the B-spline functions. The numerical experiments showed that the present method is an applicable technique and gives an exciting results for European option pricing.
Keywords: Black-Scholes equation; B-spline method; american options; valuation; amerikan seçenekleri; değerleme